2007
DOI: 10.1088/0268-1242/22/8/006
|View full text |Cite
|
Sign up to set email alerts
|

Silicon heating by a microwave-drill applicator with optical thermometry

Abstract: This paper presents a method for heating silicon wafers locally by open-end coaxial microwave applicators, with optical techniques employed for measuring the temperature. Silicon samples of ∼2 × 2 cm 2 area were radiated in air atmosphere by a microwave drill operating at 2.45 GHz in the range of 20-450 W. The rate of temperature variation was measured by the Fabry-Pérot etalon effect in samples illuminated by InGaAs lasers. The steady-state temperatures were measured by the changes in the absorption index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It is well-known that conducting materials (metals and ceramics) can be heated under the influence of microwave irradiation. It was found that Al reaches 577 °C after 6 min of microwave exposure, and Si wafer can be heated to the 450 °C within only 4 s using microwave irradiation of 350 W . Since in the current study a 900 W magnetron is used, it is reasonable to assume that the temperatures and the heating rates for Si wafer and Al foil are even larger.…”
Section: Resultsmentioning
confidence: 89%
“…It is well-known that conducting materials (metals and ceramics) can be heated under the influence of microwave irradiation. It was found that Al reaches 577 °C after 6 min of microwave exposure, and Si wafer can be heated to the 450 °C within only 4 s using microwave irradiation of 350 W . Since in the current study a 900 W magnetron is used, it is reasonable to assume that the temperatures and the heating rates for Si wafer and Al foil are even larger.…”
Section: Resultsmentioning
confidence: 89%
“…A heuristic condition for the microwave‐drill applicability can be phrased as W > D , where W is the localized microwave power absorbed in the hotspot, and D is a thermal factor given by $D_{\rm D} = 2.5k_{{\rm th}} \left( {{{d_{{\rm hs}} \Delta T} \mathord{\left/{\vphantom {{d_{{\rm hs}} \Delta T} {\Delta \varepsilon ''_{\rm r} }}} \right.\kern-\nulldelimiterspace} {\Delta \varepsilon ''_{\rm r} }}} \right)$ and $D_{\rm M} = 1.4k_{{\rm th}} \sqrt {\omega \mu _0 \sigma } \Delta Td_{{\rm hs}}^2 \,$ for dielectrics and conductors, respectively, where k th is the thermal conductivity, d hs is the hotspot diameter, ω is the microwave angular frequency, and Δ T and Δε′ r are the differences between the melting and the ambient temperatures and between the corresponding dielectric losses, respectively. This rough one‐dimensional model is valid for dielectric wafers [11] and metallic foils [13]. The condition W > D can be satisfied for most practical materials in reasonable microwave power levels, except for perfect dielectrics such as pure alumina or sapphire.…”
Section: Discussionmentioning
confidence: 99%
“…The microwave drill concentrates the microwave energy into a hotspot of ∼1‐mm diameter on the material surface by virtue of the localized thermal‐runaway effect [10]. The microwave‐drill type apparatus is used here only for the localized heating [11] without deepening the hole. The molten hotspot is further evaporated and ionized by the localized microwave field.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental setup depicted in Figure 1 a,b consist of a microwave cavity made of a WR340 waveguide with additional openings (in microwave cutoff) for diagnostics, namely for the video imaging and optical spectroscopy line-of-sight, and for the synchrotron X-ray beam passing through the plasmoid (as in [ 1 , 13 , 14 , 15 ]). The substrate made of silicon is vertically positioned as in [ 19 ]. The movable electrode directs the microwave energy locally into the substrate.…”
Section: Methodsmentioning
confidence: 99%